IMPLICATION OF CPG ISLANDS ON AGING-MEDIATED CHROMATIN ARCHITECTURE DISRUPTION. (16th November 2018) - Lee, J; Beck, S
Abstract: Aging is an inevitable process of life that causes various degenerative phenotypes in multiple tissues. Understanding the underlying mechanisms will be crucial for the development of effective treatments that delay the onset of aging-related diseases. Changes in the 3-D architecture of chromatin are the hallmark of aging. In normal nucleus, silent heterochromatin is associated with the nuclear lamina layer underlying nuclear envelop, thus spatially separated from euchromatin at nuclear center. Interestingly, the disruption of nuclear lamina and the decondensation of associated heterochromatin are commonly observed in various aging contexts. Although these structural changes have been recognized for over two decades, the exact mechanism of how they are associated with aging-mediated defects still remain unanswered. Through computational analyses of over 4, 000 NextGen sequencing data, we identified that CpG islands (CGIs) provide important clues to answering this question. Our results demonstrate that only genes without CGIs (CGI- genes) reside within the nuclear peripheral heterochromatin in the tissues where they are not expressed, while genes with CGIs primarily associate with nuclear central euchromatin even when they are transcriptionally inactive. Our data suggest that the aging-mediated decondensation of heterochromatin perturbs normal positional/epigenetic regulation of tissue-specific CGI- genes, and this in turn, results in various aging-related pathologies.